Lineage divergence at the first TCR dependent checkpoint: preferential γδ and impaired αβ T cell development in non-obese diabetic (NOD) mice() - Feng, Ni (2010)
The first TCR-dependent checkpoint in the thymus determines αβ vs. γδ T lineage fate and sets the stage for later T cell differentiation decisions. We had previously shown that early T cells in NOD mice that are unable to rearrange a TCR exhibit a defect in checkpoint enforcement at this stage. To determine if T cell progenitors from wild type NOD mice also exhibit cell-autonomous defects in development we investigated their differentiation in the Notch-ligand presenting OP9-DL1 co-culture system, as well as by analysis of T cell development in vivo. Cultured CD4 and CD8 double negative (DN) cells from NOD mice exhibited major defects in the generation of CD4 and CD8 double positive (DP) αβT cells, while γδT cell development from bipotent precursors was enhanced. Limiting dilution and single cell experiments show that the divergent effects on αβ and γδ T cell development did not spring from biased lineage choice but from increased proliferation of γδT cells and impaired accumulation of αβT lineage DP cells. In vivo, NOD early T cell subsets in the thymus also show characteristics indicative of defective β-selection, and peripheral αβT cells are poorly established in mixed bone marrow chimeras, contrasting with strong γδT as well as B cell repopulation. Thus, NOD T cell precursors reveal divergent, lineage-specific differentiation abnormalities in vitro and in vivo from the first TCR-dependent developmental choice point, which may have consequences for subsequent lineage decisions and effector functions.